2006
DOI: 10.1038/ja.2006.11
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Time-kill Activities of Rifalazil, Alone and in Combination with Vancomycin, against Logarithmic and Stationary Cultures of Staphylococcus aureus

Abstract: Rifalazil is a novel rifamycin that, like other members of this class, inhibits bacterial transcription by targeting the b subunit of prokaryotic DNA-dependent RNA polymerase. To address the high-frequency resistance seen with rifamycins, we assessed the ability of rifalazil, alone and in combination with vancomycin, to both kill cells and to suppress the appearance of resistant mutants in log and stationary phase Staphylococcus aureus cultures, using high cell densities in an in vitro kill curve model. We fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 9 publications
0
10
0
2
Order By: Relevance
“…Bactericidal activity was assessed over 24 hours using agar plate counts to determine CFU. The high initial density allowed us to monitor the appearance of rifamycin-resistant mutants, as described previously [3]. We found that for log phase (growing) cells, when compared with each drug used alone, rifalazil co-treatment with levofloxacin, linezolid, or mupirocin showed enhanced killing of S. aureus and suppression of rifamycin-resistant mutants.…”
Section: Introductionmentioning
confidence: 59%
See 4 more Smart Citations
“…Bactericidal activity was assessed over 24 hours using agar plate counts to determine CFU. The high initial density allowed us to monitor the appearance of rifamycin-resistant mutants, as described previously [3]. We found that for log phase (growing) cells, when compared with each drug used alone, rifalazil co-treatment with levofloxacin, linezolid, or mupirocin showed enhanced killing of S. aureus and suppression of rifamycin-resistant mutants.…”
Section: Introductionmentioning
confidence: 59%
“…In this set of experiments, cultures were followed for at least 24 hours, and those that showed any trend toward decreased viability at 24 hours were followed for an additional 24 hours. Rifalazil plus vancomycin, previously shown to have activity against stationary phase cells [3] and therefore used as a positive control, again showed effective bactericidal activity. Our data indicate that the rifalazil-vancomycin combination appears to be thus far uniquely effective against non-growing S. aureus.…”
Section: Treatment Of Stationary Phase (Non-growing) S Aureusmentioning
confidence: 89%
See 3 more Smart Citations